2017
DOI: 10.1016/j.agee.2017.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Lime and phosphogypsum impacts on soil organic matter pools in a tropical Oxisol under long-term no-till conditions

Abstract: Improving soil organic matter (SOM) quality in tropical acid soils is important for increasing the sustainability of agricultural ecosystems. This research evaluated the effect of the surface application of lime and phosphogypsum on the quality and amount of SOM in a long-term crop rotation under no-till conditions. The research was performed in a kaolinitic, thermic Typic Haplorthox for 12 years with annual crops under no-till. The treatments included no soil amendments, and amendment with phosphogypsum, lime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 45 publications
3
15
0
1
Order By: Relevance
“…Similarly, oyster shell powder has a significant effect on improving the soil pH [ 18 ]. These improvements in soil profile result in providing a better soil environment for the functioning of soil microbiota through the addition of lime [ 13 , 19 ], gypsum [ 12 , 20 ], mushroom residue [ 21 ], and oyster shell powder [ 18 , 22 ]. Magnesium (Mg) fertilizers have also been used to increase the soil pH, and earlier studies have also shown that their addition into the soil has a significant effect on soil physicochemical properties and microbial communities [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, oyster shell powder has a significant effect on improving the soil pH [ 18 ]. These improvements in soil profile result in providing a better soil environment for the functioning of soil microbiota through the addition of lime [ 13 , 19 ], gypsum [ 12 , 20 ], mushroom residue [ 21 ], and oyster shell powder [ 18 , 22 ]. Magnesium (Mg) fertilizers have also been used to increase the soil pH, and earlier studies have also shown that their addition into the soil has a significant effect on soil physicochemical properties and microbial communities [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The decomposition rate constant (k) was regulated by environmental factors and soil conditions (Campbell et al 1994). Previous studies indicated that liming could increase the turnover rate of soil organic matter due to increase in soil pH thus facilitating microbial activity (Carmeis Filho et al 2017;Lochon et al 2018). Soil pH is considered as a key factor governing the microbial turnover of organic carbon (Bertrand et al 2007;Xiao et al 2018).…”
Section: Effect Of Dolomite Particle Size On Soc Turnover Ratementioning
confidence: 99%
“…Changes in pH, substrate, and nutrient availabilities for microbes in the soil after liming can affect SOC mineralization. In general, liming has positive effects on SOC mineralization since it can ameliorate soil acidity and has the potential to increase microbial activity (Adams and Adams 1983;Carmeis Filho et al 2017). Increase in soil pH may increase dissolved organic carbon (DOC), which can be rapidly mineralized (Ahmad et al 2013;Marcelo et al 2012), and induces a microbial respiratory flush in the first few days following lime application (Fuentes et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ is an environmentally ubiquitous cation that could potentially play an important role in the stabilization of SOC (Rowley et al, 2018). Ca is a plant macronutrient and there is evidence that Ca also has localized positive effects on net primary productivity and SOC inputs through aboveground and belowground biomass (Carmeis Filho, Penn, Crusciol, & Calonego, 2017). Therefore, leaching of Ca resulting from increasing precipitation may lead to a decrease of SOC concentration in the Tibetan Plateau shrublands.…”
Section: Effects Of Climatic Factors On Soc Concentration In the Tibetan Plateau Shrublandsmentioning
confidence: 99%